Economic Impact of Nonmodifiable Risk Factors in Orthopaedic Fracture Care: Is Bundled Payment Feasible?. Issue 3 (March 2017) - Mahure, Siddharth A.; Hutzler, Lorraine; Yoon, Richard S.; Bosco, Joseph A.
Abstract : Objectives: To determine whether bundled payments are feasible in the orthopaedic fracture setting, and the potential economic implications of this reimbursement structure. Design: Prospective. Setting: Multicenter. Patients/Participants: Between 2004 and 2014, a total of 23, 643 operatively treated patients with fracture and 544, 067 patients with total joint arthroplasty (TJA) were identified using the New York State Statewide Planning and Research Cooperative System database. Interventions: Severity of illness (SOI), hospital charges ($USD), length of stay (LOS; days), and discharge disposition (homebound vs. not) were collected. Main Outcome Measurements: Patients were subdivided into groups of minor and severe SOI. Differences in hospital charges, LOS, and discharge disposition were analyzed. Differences in charges, LOS, and discharges were further analyzed based on minor and severe SOI. Results: The difference in hospital charge between patients with minor or severe SOI undergoing elective TJA ranged between 153% and 211%. In contrast, patients undergoing fracture surgery exhibited differences ranging from 314% to 489% between minor and severe SOI levels. Similar differences were observed regarding mean hospital LOS and homebound discharge disposition, with patients with fracture demonstrating greater sensitivity to increasing SOI. Conclusions: Although bundled payments may be a viable option for patients undergoing elective TJA, this payment model requires particular attention when applied to fracture care.